Efektivitas Media Pembelajaran Interaktif dalam Meningkatkan Minat Belajar Siswa SD - Serli Sapitri; Ari Suriani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this study is to evaluate how well interactive learning materials can raise elementary school pupils' motivation and interest in learning. Animation films, instructional games, and simulations are examples of interactive learning materials that offer students a familiar, dynamic, and developmentally appropriate learning experience. Using a qualitative approach and a literature review strategy, the study examined material from a range of pertinent sources, including books, journals, and research reports. According to the study's findings, students who actively interact with interactive media can become more involved in the learning process. Additionally, it offers instant feedback, which increases self-confidence, helps pupils understand their progress, and fortifies their enthusiasm to learn.